The Role of Medical Ethics In Comprehensive Healthcare System - Zali, Alireza (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
Daily development of the human knowledge, promotion of biomedical technologies and improvement of physicians' ability in diagnosis and treatment of different types of diseases have always accompanied plenty of discussions and challengeable subjects, especially from the view point of ethical issues. Obtaining deep and accurate recognition of these subjects, the attention of the physicians and the scholars of different fields, especially of the ethics has been drawn to medical ethics as a new solution in the comprehensive Healthcare System. Despite the great changes in medical technologies, there are still some concerns about the physicians' abilities in decision makings that may directly or indirectly affect the health or life of the people. Therefore these concerns have leaded to the appearance of new movements all calling for the patients' rights and the rights of society to participate in medical decision-makings. On the other hand we should notice about some other cases that play effective roles in policy makings of the comprehensive healthcare system. Fore instance, the required resources will vary following the changes in technology; the population especially of the elderly is increasing; moreover the time needed for the new work forces to be entered into the labor market has typically increased. Consequently, a higher number of people are waiting to benefit from the recourses and lower number of them is involved in producing the recourses. Thus, to work on the important topics like the requirements of human societies, ethical considerations of biotechnology and medical researches, Allocation of limited and immense resources, important ethical criteria of decision makings, representation of fundamental solutions and medical ethics trainings is considered as one of the most basic necessities of comprehensive healthcare system among others.